Kehadiran Kapal Patroli Pangkalan TNI AL Terhadap Pengendalian Laut di Selat Lombok - Agung Ariwibowo (Institut Transportasi dan Logistik Trisakti, 2019)
Sea security means that the sea can be controlled and safely used by users to be free from threats or disturbances to its use. The Navy Base is an integral part of the Integrated Armed Weapon System (SSAT) which has an additional function to carry out security in its work area in the form of limited sea security operations (opskamlatas). The Lombok Strait is one of the important Choke Points with heavy shipping traffic, so security in the strait needs to be guaranteed by sea control by the Navy's base elements. The purpose of this study was to analyze the effect of the ability of limited sea security operations to control the sea in the Lombok Strait with the presence of a Navy Base patrol boat in the Lombok Strait. The method used in this study is a quantitative method with population at the Navy base in the Lombok Strait. The results of the research that have been carried out are the significant influence of the presence of patrol ships of the Indonesian Navy Base on sea control in the Lombok Strait.